Strategi Pengembangan Produk dan Komunikasi Pemasaran Dalam Meningkatkan Omset Penjualan di Masa Pandemic Pada PT. Ervamies Makmur Pratama - Diah Lukitasari; Baiq Herdina Septika (Yayasan Pendidikan Intan Cendekia, 2023)
This study aims to determine the product development strategy and to determine the communication system that is run by PT. Ervamies Makmur Pratama during the covid-19 period. This research uses a qualitative case study method that produces descriptive data while the data collection techniques are carried out by observation, interviews, and documentation techniques, product development strategies and communication systems that are carried out by PT. Ervamies Makmur Pratama to stay afloat in the midst of the covid-19 pandemic, namely the 4P marketing mix (product, promotion, price, and place) and the communication system using offline and online, using sales marketing and Facebook and Whatsapp. The product development strategy is carried out by PT. Ervamies Makmur Pratama as a promotional strategy to attract buyers/customers by holding discounts, discount prices. Based on the research described by the researcher that the strategy and communication system carried out by PT. Ervamies Makmur Pratama sales income has retumed to normal in 2022 and always provides satisfactory service to customers.